Inhibition of RACK1‐Mediated NLRP3 Oligomerization (Active Conformation) Ameliorates Acute Respiratory Distress Syndrome - Jian Cui; Meng Yang; Chengli Yu; Haidong Zhang; Yuan Gong; Yang Hu; Yue Wang; Qingxin Yuan; An Pan; Jiepin Li; Yaowen Hu; Zecheng Jin; et al. (Advanced Science, 2025)
Abstract Aberrant activation of the NACHT, LRR, and PYD domain‐containing protein 3 (NLRP3) inflammasome contributes to the pathogenesis of fatal and perplexing pulmonary diseases. Although pharmacological inhibition of the NLRP3 inflammasome brings potent therapeutic effects in clinical trials and preclinical models, the molecular chaperones and transition governing its transformation from an auto‐suppressed state to an active oligomer remain controversial. Here, this work shows that sesquiterpene bigelovin inhibited NLRP3 inflammasome activation and downstream pro‐inflammatory cytokines release via canonical, noncanonical, and alternative pathways at nanomolar ranges. Chemoproteomic target identification discloses that bigelovin covalently bound to Cys168 of RACK1, disrupting the interaction between RACK1 and NLRP3 monomer and thereby suppressing NLRP3 inflammasome oligomerization in vitro and in vivo. Bigelovin treatment significantly alleviates the severity of NLRP3‐related pulmonary disorders in murine models, such as LPS‐induced ARDS and silicosis. These results consolidated the intricate role of RACK1 in transiting the NLRP3 state and provided a new anti‐inflammatory lead and therapy for NLRP3‐driven diseases.